Evolución de la financiación de los medios de comunicación en España. ¿Hacia un modelo más sostenible? - Colino Fernández, Alberto (Papeles de Europa, 2013)
The access to information is a right that our Constitution recognizes and protects as a fundamental right of every person. From this standpoint, Government subsidies to mass media have a foundation that justifies them as a mean to guarantee the provision of a sufficient number of plural media available to citizens. Nevertheless, detractors of subsidies argue that they entail a waste of resources –since the market guarantees that the most efficient will survive- and the interference of the Government of the moment on mass media. Therefore, this article analyses the changes happened in the evolution of the funding model of mass media in Spain in recent years, and particularly the increasing relevance of subsidies, in order to be able to characterize its current condition and suitability to achieve the goals that it pursues.